A comprehensive review and update on ulcerative colitis - Gajendran, Mahesh; Loganathan, Priyadarshini; Jimenez, Guillermo; Catinella, Anthony P.; Ng, Nathaniel; Umapathy, Chandraprakash; Ziade, Nathalie; Hashash, Jana G. (Disease-a-month, 2019)
Ulcerative colitis (UC) is a chronic idiopathic inflammatory bowel disorder of the colon that causes continuous mucosal inflammation extending from the rectum to the more proximal colon, with variable extents. UC is characterized by a relapsing and remitting course. UC was first described by Samuel Wilks in 1859 and it is more common than Crohn's disease worldwide. The overall incidence and prevalence of UC is reported to be 1.2–20.3 and 7.6–245 cases per 100,000 persons/year respectively. UC has a bimodal age distribution with an incidence peak in the 2nd or 3rd decades and followed by second peak between 50 and 80 years of age. The key risk factors for UC include genetics, environmental factors, autoimmunity and gut microbiota. The classic presentation of UC include bloody diarrhea with or without mucus, rectal urgency, tenesmus, and variable degrees of abdominal pain that is often relieved by defecation. UC is diagnosed based on the combination of clinical presentation, endoscopic findings, histology, and the absence of alternative diagnoses. In addition to confirming the diagnosis of UC, it is also important to define the extent and severity of inflammation, which aids in the selection of appropriate treatment and for predicting the patient's prognosis. Ileocolonoscopy with biopsy is the only way to make a definitive diagnosis of UC. A pathognomonic finding of UC is the presence of continuous colonic inflammation characterized by erythema, loss of normal vascular pattern, granularity, erosions, friability, bleeding, and ulcerations, with distinct demarcation between inflamed and non-inflamed bowel. Histopathology is the definitive tool in diagnosing UC, assessing the disease severity and identifying intraepithelial neoplasia (dysplasia) or cancer. The classical histological changes in UC include decreased crypt density, crypt architectural distortion, irregular mucosal surface and heavy diffuse transmucosal inflammation, in the absence of genuine granulomas. Abdominal computed tomographic (CT) scanning is the preferred initial radiographic imaging study in UC patients with acute abdominal symptoms. The hallmark CT finding of UC is mural thickening with a mean wall thickness of 8 mm, as opposed to a 2–3 mm mean wall thickness of the normal colon. The Mayo scoring system is a commonly used index to assess disease severity and monitor patients during therapy. The goals of treatment in UC are three fold—improve quality of life, achieve steroid free remission and minimize the risk of cancer. The choice of treatment depends on disease extent, severity and the course of the disease. For proctitis, topical 5-aminosalicylic acid (5-ASA) drugs are used as the first line agents. UC patients with more extensive or severe disease should be treated with a combination of oral and topical 5-ASA drugs +/− corticosteroids to induce remission. Patients with severe UC need to be hospitalized for treatment. The options in these patients include intravenous steroids and if refractory, calcineurin inhibitors (cyclosporine, tacrolimus) or tumor necrosis factor-α antibodies (infliximab) are utilized. Once remission is induced, patients are then continued on appropriate medications to maintain remission. Indications for emergency surgery include refractory toxic megacolon, colonic perforation, or severe colorectal bleeding.